Pengaruh Total Quality Management pada Sistem Pengukuran Kinerja Terhadap Pengembangan Produk dan Efisiensi Biaya: Studi Kasus pada PT Bintang Alam Semesta - Meyliana -; Agus Yoan Renata (Universitas Kristen Maranatha, 2012)
The growing global competition will encourage firms to try to maintain their competitive advantage. One way that can be done by giving full attention to the quality. With regard to this, so this research tries to identify the variables that affect the quality of a company's products. The variables used include Total Quality Management (TQM) and performance measurement systems. Performance measurement system include product development and cost efficiency. Samples taken by using purposive sampling method. The purpose of this research was to 1) know how much influence TQM in measuring performance, improving cost efficiency, and perform product development in the company's operations; 2) to determine the importance of the role of TQM in improving the company's competitive advantage; and 3) to determine strengths and weaknesses in the practice of TQM. The results showed that performance measurement systems have a positive impact on Total Quality Management.